Case Report: Successful Treatment of a Child With COVID-19 Reinfection-Induced Fulminant Myocarditis by Cytokine-Adsorbing oXiris® Hemofilter Continuous Veno-Venous Hemofiltration and Extracorporeal Membrane Oxygenation - Phuc H. Phan; Dung T. Nguyen; Nam H. Dao; Ha T. T. Nguyen; An V. Vu; Son T. Hoang; Lam V. Nguyen; Tung V. Cao; Dien M. Tran (Frontiers Media S.A., 2022)
BackgroundIndirect cardiomyocyte damage-related hyperinflammatory response is one of the key mechanisms in COVID-19-induced fulminant myocarditis. In addition to the clinical benefit of using cytokines absorption hemofiltration, the effectiveness of instituting veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support for cardiac compromise has been reported. However, current literature enunciates a paucity of available data on the effectiveness of these novel modalities.Case PresentationWe reported a 9-year-old boy with recurrent COVID-19 infection-causing fulminant myocarditis, who was treated successfully by using novel modalities of oXiris® hemofilter continuous venovenous hemofiltration (CVVH) and VA-ECMO. The patient made a full recovery without any sequelae.ConclusionWe conclude that the novel highly-absorptive hemofilter CVVH and VA-ECMO may be effective treatment modalities in managing SARS-CoV-2-induced fulminant myocarditis. Our report highlights the need for further well-designed investigations to confirm this extrapolation.